Intelligent wireless communications - Mastorakis, George; Mavromoustakis, Constandinos X.; Mongay Batalla, Jordi; Pallis, Evangelos (Institution of Engineering & Technology, 2021)
Aimed at researchers, engineers and scientists involved in the design and development of protocols and AI applications for wireless communication devices and networks, this edited book presents recent research and innovations in emerging AI methods and AI-powered mechanisms, and future perspectives in this field
Keywords: Artificial intelligence.; Wireless communication systems.; elektronické knihy; electronic books